The Buy & Sell Strategy with Concept of"Standart Contract" & Problems - Sukarmi Sukarmi; Djauhari Djauhari; Denny Suwondo (Jurnal Akta, 2020)
The impact of globalization penetrates various aspects of life and layers, especially in the field of trade (buying and selling). This field is vulnerable to the use of standard agreements to facilitate transactions with standard or standard contract receipts, meaning that the clauses are drawn up and arranged in such a way without paying attention to the interests of consumers as users of goods and/services. There is an injustice in the process of making the agreement, because the consumer is not involved in determining the agreement, resulting in extreme emotions, different perceptions of the object of the dispute, and ultimately unpleasant attitudes between the parties. The urgency of research to get the right solution in getting around is made possible through Alternative Dispute Resolution (dispute resolution out of court), juridical normative method with descriptive analytical research specifications. Analyzing the problem by describing factually related to existing legal norms. Social Justice Theory which is in line with John Rawls' opinion, justice which focuses on the balance of rights and obligations of the parties, so that it has the opportunity to consistently benefit.